A palmitate-rich metastatic niche enables metastasis growth via p65 acetylation resulting in pro-metastatic NF-κB signaling - Altea-Manzano, Patricia; Doglioni, Ginevra; Liu, Yawen; Cuadros, Alejandro M; Nolan, Emma; Fernández-García, Juan; Wu, Qi; Planque, Mélanie; Laue, Kathrin Julia; Cidre-Aranaz, Florencia; Liu, Xiao-Zheng; Marin-Bejar, Oskar; et al. (Nature cancer, 2023)
Metabolic rewiring is often considered an adaptive pressure limiting metastasis formation; however, some nutrients available at distant organs may inherently promote metastatic growth. We find that the lung and liver are lipid-rich environments. Moreover, we observe that pre-metastatic niche formation increases palmitate availability only in the lung, whereas a high-fat diet increases it in both organs. In line with this, targeting palmitate processing inhibits breast cancer-derived lung metastasis formation. Mechanistically, breast cancer cells use palmitate to synthesize acetyl-CoA in a carnitine palmitoyltransferase 1a-dependent manner. Concomitantly, lysine acetyltransferase 2a expression is promoted by palmitate, linking the available acetyl-CoA to the acetylation of the nuclear factor-kappaB subunit p65. Deletion of lysine acetyltransferase 2a or carnitine palmitoyltransferase 1a reduces metastasis formation in lean and high-fat diet mice, and lung and liver metastases from patients with breast cancer show coexpression of both proteins. In conclusion, palmitate-rich environments foster metastases growth by increasing p65 acetylation, resulting in a pro-metastatic nuclear factor-kappaB signaling.
Keywords: Animals; NF-kappa B; acetylkoenzym A; palmitany; Acetyl Coenzyme A; lysinové acetyltransferasy; acetylace; Mice; Acetylation; Palmitates; Carnitine O-Palmitoyltransferase; Lysine Acetyltransferases; myši; karnitin-O-palmitoyltransferasa; zvířata